ANALISIS MANAJEMEN LOGISTIK DAN PENGENDALIAN PERSEDIAAN BAHAN BAKU PISANG BOLEN (Studi Kasus pada CV Mayang Sari Kota Bandar Lampung) - Fahira, Frisky; Haryono, Dwi; Sari, Dewi Mulia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
Logistics management is important for agro-industries as it controls raw material inventory to ensure smooth and sustainable operations.  This research was a case study that aimed to evaluate delivery time, to analyze the percentage of logistics costs of the revenue of banana bolen products, and to analyze inventory management at CV Mayang Sari in Bandar Lampung City.  The analysis methods used were delivery time analysis using the On Time In Full (OTIF) matrix, logistics cost analysis, and inventory management analysis using the deterministic Economic Order Quantity (EOQ) method.  The results show that the OTIF value at CV Mayang Sari in 2023 is 89 percent.  This value indicated that the delivery time performance of CV Mayang Sari is categorized as good.  The total logistics cost of CV Mayang Sari’s banana bolen in 2023 is IDR894,116 with the percentage of logistics costs to revenue is 0.52 percent.  This figure indicates that logistics management at CV Mayang Sari is efficient.  Based on the inventory management analysis using the deterministic EOQ method, it is  recommended that the optimal order quantity is 1,330 bunches per month for four times order, the safety stock for banana raw materials is 28 bunches, and the reorder point occurred when the inventory level reached 115 bunches.  Based on the EOQ analysis, the total inventory cost is IDR1,215,679 per  year, enabling  the agroindustry to save the inventory costs IDR7,290,321 per year.   Keywords: agroindustry, bolen banana, delivery time, EOQ, logistics cost, OTIF